2016
DOI: 10.17116/oftalma2016132581-85
|View full text |Cite
|
Sign up to set email alerts
|

. Oсumethyl in the treatment of allergic diseases of eyelids and conjunctiva

Abstract: Treatment of allergic diseases of eyelids and conjunctiva (conjunctivites and blepharoconjunctivites) often presents difficulties due to peculiarities of their pathogenesis - allergic and vascular reactions, disorder of lacrimal production, meibomian gland dysfunction, and possible bacterial contamination. It has been suggested to use Ocumethyl, which contains zinc sulfate (binding, drying, anti-inflammatory, and antiseptic effect), diphenhydamine hydrochloride (an Н1-antihistamine that decreases capillary per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“… 27 Nonprescription topical ophthalmic medications containing MB are commonly used internationally for various complaints of ocular discomfort and redness. Marchenko 34 reported a clinically significant effect with an ophthalmic solution containing zinc sulfate, diphenhydramine hydrochloride, naphazoline hydrochloride, and MB (300 ng/mL) in patients with chronic allergic conjunctivitis, blepharo-conjunctivitis, or contact lens induced giant papillary conjunctivitis following treatment (3 times daily for 15–30 days). Brownstein et al 35 reported 6 patients with a spectrum of adverse ocular reactions, following prolonged daily use (4 months to 8 years) of nonprescription topical ophthalmic medication composed of MB, naphazoline hydrochloride or nitrate, and amylocaine hydrochloride, that were presumably due to at least one of the ingredients.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Nonprescription topical ophthalmic medications containing MB are commonly used internationally for various complaints of ocular discomfort and redness. Marchenko 34 reported a clinically significant effect with an ophthalmic solution containing zinc sulfate, diphenhydramine hydrochloride, naphazoline hydrochloride, and MB (300 ng/mL) in patients with chronic allergic conjunctivitis, blepharo-conjunctivitis, or contact lens induced giant papillary conjunctivitis following treatment (3 times daily for 15–30 days). Brownstein et al 35 reported 6 patients with a spectrum of adverse ocular reactions, following prolonged daily use (4 months to 8 years) of nonprescription topical ophthalmic medication composed of MB, naphazoline hydrochloride or nitrate, and amylocaine hydrochloride, that were presumably due to at least one of the ingredients.…”
Section: Discussionmentioning
confidence: 99%